Applications of Laparoscopic Transperitoneal Surgery of the Pediatric Urinary Tract - Szavay, Philipp O. (Frontiers in Pediatrics, 2019)
Application of laparoscopy in pediatric urology has evolved over more than 30 years coming from a merely diagnostic use for non-palpable testes to "interventional" laparoscopy to extirpative surgery and finally to the era of reconstructive pediatric laparoscopic urology, when in 1995 Peters described the first laparoscopic pyeloplasty in a child. Laparoscopic surgery in pediatric urology became implemented increasingly in the 21st century with now present-day applications including the complete variety of all kind of indications for surgery for pediatric urological pathology. This article aims to provide a comprehensive overview of current indications, techniques and outcomes of laparoscopic transperitoneal surgery of the upper as well as of the lower urinary tract for urological pathology in the pediatric patient population.